Fluxo lateral na infiltração de água medida com duplo anel concêntrico - Boeno, Daniel (2019)
The basic infiltration rate (TIB) is important in the definition of the irrigation rate and in the planning of soil conservation systems. The TIB’s estimate has often been made with a double concentric ring, due to its easy usage and low cost. However, there is evidence that the rate of stable infiltration measured by the double concentric ring (TIEAC) is greater than that determined by other methods and it overestimates the TIB. The hydraulic load present on the soil surface and the absence of formation or increase of the surface sealing are particularities of the method that favor the overestimation of the TIB. However, a gap that has not been explored yet is whether the lateral flow inside the profile, especially in heterogeneous soil profiles, may be a major cause of the overestimation of TIB by TIEAC. A way of detecting the existence of lateral flow is to verify if there are differences in measured TIEAC at different depths. Using this strategy, the objective of this study was to investigate if there is any disagreement between TIEAC and the saturated flow measured at different depths of the soil profile. TIEAC measurements were made at the top of horizons A, E and Bt (pedogenetic factor), in an experimental area with compacted, scarified soil conditions, and absence of both (anthropic factor). There was no effect of soil conditions in the TIEAC, probably because the measurements occurred 7 months after the establishment of the conditions. It was possible to detect the pedogenetic interference in the TIEAC, because the TIEAC of the horizon A was 10 times greater than the Bt, which is considered the most restrictive. The decrease of the TIEAC in depth indicates that the TIEAC measured at the soil surface is an overestimation of the TIB.